Improving Students' Speaking Skills through Debate Technique at SMA IT Wahdah Islamiyah Makassar - Mumin, Mumin; Tahir, Muh.; Sally, Fauzan Hari Sudding (Journal of Excellence in English Language Education, 2026)
This study evaluates the impact of the Debate technique on enhancing the speaking skills of students, specifically in vocabulary, pronunciation, and fluency. Conducted at SMA IT Wahdah Islamiyah Makassar, the research employed a pre-experimental design with a one-group pre-test and post-test setup, involving 20 students from Class XI.2 selected via cluster random sampling. Data were gathered through speaking tests administered before and after the intervention, with the Debate technique applied over four sessions. Data analysis revealed a significant improvement in speaking skills, with the mean score rising from 63 in the pre-test to 77 in the post-test, a 22% improvement. The t-test yielded a significance value of 0.000 (<0.05), confirming the effectiveness of the Debate technique. Notable improvements included vocabulary (24%), pronunciation (24%), and fluency (19%). Thus, the Debate technique is an effective approach for enhancing speaking skills among students at SMA IT Wahdah Islamiyah Makassar.